Diagnostic Imaging of Hepatocellular Carcinoma - A Pictorial Essay - K. Nowicki, Tomasz; Markiet, Karolina; Szurowska, Edyta (Current Medical Imaging, 2017)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer, which develops mostly in the setting of chronic liver disease. European Association for the Study of the Liver (EASL) and European Organization for Research and Treatment of Cancer (EORTC) prepared guidelines for screening, follow-up and diagnosis of HCC to facilitate decision making and optimize both diagnostic and therapeutic protocols. The review briefly describes etiology, epidemiology and histopathology of HCC and presents EASL-EORTC guidelines for surveillance and diagnosis of HCC. Target population and screening algorithm is presented in the surveillance section. Ultrasound imaging of HCC and the role of contrast enhanced ultrasound are described as well as the value of laboratory tests in screening. Further, radiological features of HCC in multiphase CT and dynamic contrast enhanced MRI and diagnostic criteria are presented. Additionally, the advantages of advanced techniques in MRI such as diffusion weighed imaging and the use of hepatocyte-specific contrast agents are discussed. Lastly, the EASL-EORTC guidelines are compared with the guidelines of the American Association for the Study of Liver Diseases and the Japan Society of Hepatology. Also LI-RADS and the Barcelona Clinic Liver Cancer classification are mentioned. In the near future, due to the ongoing advances in imaging a revision of the guidelines may be expected.
Keywords: diagnostic algorithm